2013
DOI: 10.4314/agrosh.v13i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Hatch-Out Analysis and Repeatability Estimates of Common Hatchability Problems in Issa-Brown Breeder Stock

Abstract: Six thousand and three hundred (6,300) sampled hatchable eggs (from a total of 68,130 eggs) produced in two commercial farms were used to evaluate hatchout performance and repeatability of some common hatchability problems in 38-41 weeks old Isa-Brown hens. Fertility, hatchability of total egg set and hatchability of fertile eggs were generally high (>80%) for eggs from the two farms. There was significant difference (p<0.05) between the two farms in the magnitude of hatchability problems at the early (1-7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Presumably, this may be attributed to breeding and hatchery problem. Fayeye and Olapade (2013) reported that incidence of small chicks was attributable to farm source of hatchable eggs as well as on the type and magnitudes of reproductive failures that occurred during incubation. The small size of chicks which they maintained throughout the experimental period could have accounted for the generally low feed intake observed in the control and BRCM based diets.…”
Section: Microbiological Assaymentioning
confidence: 99%
“…Presumably, this may be attributed to breeding and hatchery problem. Fayeye and Olapade (2013) reported that incidence of small chicks was attributable to farm source of hatchable eggs as well as on the type and magnitudes of reproductive failures that occurred during incubation. The small size of chicks which they maintained throughout the experimental period could have accounted for the generally low feed intake observed in the control and BRCM based diets.…”
Section: Microbiological Assaymentioning
confidence: 99%
“…The results of the four full incubation trials showed that combining both convective and radiative heating mechanisms was successful to hatch the incubated eggs with average hatch-of-fertile (HOF = (hatched chicks/number of true fertile eggs) × 100) of 84.0% (±0.5). A breakout of the unhatched eggs was performed [35,36] in the end of each incubation trial. The average breakout results of the unhatched eggs are shown in Figure 12.…”
Section: Mpc Implementation and Full Incubation Experimentsmentioning
confidence: 99%